2015
DOI: 10.1007/s00540-015-2045-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting survival in pediatric cardiac tamponade caused by central venous catheters

Abstract: Pediatric central venous catheter (CVC) placement is useful but associated with complications such as cardiac tamponade. We aimed to identify risk factors for death in cardiac tamponade. Published articles on pediatric CVC-associated cardiac tamponade were obtained by searching PubMed and Google and retrospectively reviewed to analyze risk factors for death. Factors examined for their effect on mortality risk included patient age, weight, CVC size, days from CVC insertion to tamponade occurrence, substances ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…In our study, three out of the four cases were extremely premature neonates, with extremely low birth weight. Nevertheless, studies have not discovered a correlation between gestational age or weight and the incidence of tamponade secondary to neonatal PICC (14)(15)(16). The management of pericardial effusions is controversial and greatly depends on the size of the effusions and the patient's clinical status.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, three out of the four cases were extremely premature neonates, with extremely low birth weight. Nevertheless, studies have not discovered a correlation between gestational age or weight and the incidence of tamponade secondary to neonatal PICC (14)(15)(16). The management of pericardial effusions is controversial and greatly depends on the size of the effusions and the patient's clinical status.…”
Section: Discussionmentioning
confidence: 99%
“…PCE/CT has a variety of clinical manifestations, such as dyspnea, bradycardia, and hypotension; however, owing to the lack of specific clinical manifestations, the diagnosis of PCE/CT is difficult, and without immediate treatment, the mortality rate is often high. The currently known risk factors for PICC-induced PCE/CT include catheter tip position, catheter drift, and infusion of hypertonic fluid (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that there is no difference in the risk of death from cardiac tamponade related to PICC for factors such as gestational age and weight 16,17 . Regarding general mortality among newborns with this condition, Nowlen et al 16 12,20,21 , reviews or meta-analyzes [15][16][17] . In the last 13 years, there have been original studies evaluating the complications related to the use of PICC 7,8,19,22 .…”
Section: Discussionmentioning
confidence: 99%